Market Share Analysis and Export Performance of Indonesian Crude Palm Oil in the EU Market - Jamilah, Jamilah; Zahara, Hafni; Kembaren, Emmia Tambarta; Budi, Setia; Nurmala, Nurmala (International Journal of Energy Economics and Policy, 2022)
This study aims to analyze the market share and export performance of Indonesian Crude Palm Oil (CPO) to the European Union Market, using time series data (2000 – 2020). The Market Share Index is used to assess the condition of the Indonesian CPO market in export destination countries when compared to its competitors (Malaysia). Analysis of the performance of CPO products in the European Union market using the Constant Market Share (CMS) approach. The results show that the average growth of Indonesia’s export standards to Europe is 0.1526, indicating that Indonesia is able to take advantage of CPO export opportunities. Indonesia has been able to meet CPO product specification standards in importing countries, including the Roundtable Sustainable Palm Oil (RSPO) and Hazard Analysis and Critical Control Points (HACCP) certifications as standards for safety and consumer protection. Indonesian CPO is well positioned in Spain (0.000244) and Italy (0.00014), and less well positioned in the Netherlands and Germany. Indonesia does not have good competitiveness against CPO exports in the European Union market, which causes Indonesia to shift the Asian market as the target market for Indonesian CPO.